2010
DOI: 10.1021/ie100217k
|View full text |Cite
|
Sign up to set email alerts
|

Bridging Gravimetric and Electrochemical Approaches To Determine the Corrosion Rate of Metals and Metal Alloys in Cooling Systems: Bench Scale Evaluation Method

Abstract: The gravimetric weight loss method and the electrochemical polarization resistance methods were combined to evaluate instantaneous corrosion rates for metals and metal alloys in industrial cooling-water systems. Metal and metal−alloy samples were exposed to synthetic cooling water in a bench-scale recirculating system constructed to study corrosion under flow conditions similar to those of a cooling-water system. The measurements yielded by both methods were related through a coefficient, B′, to convert polari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 9 publications
1
28
0
Order By: Relevance
“…where j WL is the corrosion current found on the mass loss measurement. Assuming a constant value (with time > 3 days) of the 'apparent' Stern-Geary coefficient (B ) for a given metal/environment system [66], it follows: Table 4 lists the B values, empirically calculated from a comparison between the EIS data (R t and R p resistances) and mass loss measurement (Q W L a ) of AZ31 tested samples after removal of the corrosion products. The change in the corrosion current density (Equation (4)) as a function of the immersion period of AZ31B in Ringer's solution (at 37 • C) is shown in Figure 8.…”
Section: Eis Diagramsmentioning
confidence: 99%
See 1 more Smart Citation
“…where j WL is the corrosion current found on the mass loss measurement. Assuming a constant value (with time > 3 days) of the 'apparent' Stern-Geary coefficient (B ) for a given metal/environment system [66], it follows: Table 4 lists the B values, empirically calculated from a comparison between the EIS data (R t and R p resistances) and mass loss measurement (Q W L a ) of AZ31 tested samples after removal of the corrosion products. The change in the corrosion current density (Equation (4)) as a function of the immersion period of AZ31B in Ringer's solution (at 37 • C) is shown in Figure 8.…”
Section: Eis Diagramsmentioning
confidence: 99%
“…This difference should be attributed to the variance in the chemical composition of both tested solutions: The Ringer's solution contains four times lower chloride concentration (0.15 M NaCl and with additional compounds) and the experiments were performed at higher temperature (37 • C). The nature of the metal or alloys and the specific corrosive environment could influence the value of B [66], which correlates to the R p and the instantaneous corrosion rate. The results of our study suggest that the chloride concentration in the test solution is a critical factor for the Stern-Geary coefficient B .…”
Section: Correlation Between Corrosion Current Densities Estimated Bymentioning
confidence: 99%
“…Under the assumption that B does not change with time for a metal or a metal alloy in a certain aqueous solution [39], one can obtain ( )…”
Section: "Apparent" Stern and Geary Values Obtained From The Correlatmentioning
confidence: 99%
“…Bland et al [26] noted that because of the rapid corrosion rates normally observed for the Mg system, the Tafel characteristics can change dramatically between a short-and long-term test. Hsieh et al [39] examined the relationship between weight loss (WL) measurements and polarization resistance measurements of corrosion in metals and metal alloys (mild steel, aluminum, copper, and cupronickel) commonly used in industrial cooling systems. The experimentally measured proportionality constant B', based on the correlation between electrochemically and gravimetric measured corrosion rates, changes with the exposure time until steady state is reached, which may take up to 3 days.…”
Section: Introductionmentioning
confidence: 99%
“…Corrosion measurements were performed using the combination of gravimetric weight loss and electrochemical polarization resistance measurements to determine average and instantaneous corrosion rates (Hsieh et al, 2010a). For electrochemical measurement in the bench-scale water recirculating system, the pipe rack was equipped to accommodate a reference electrode (RE) and a counter electrode (CE).…”
Section: Methodsmentioning
confidence: 99%